Noun-verb conversion between the poles of predictability and idiosyncrasy: How do denominal verbs build their argument structures? - Heike Baeskow (Zeitschrift für Wortbildung)
This article addresses the controversial question how non-derived denominal verbs (e.g. wingsuit, kennel, trombone) build their argument structures. Based on selected subsets of conceptually related verbs it will be shown that the argument structures of these verbs are flexible though not arbitrary. Without context, these verbs evoke frame-like default situations which are determined by speakers' shared encyclopaedic knowledge and sensorimotor experience and which are mapped onto a small set of abstract event schemata that 'predesign' thematic configurations. The discourse context, which also provides the syntactic context, either meets or models our expectations as to the context-free readings. In the latter case, new (metaphorical) readings are contextually created. These configurations are not arbitrary either because the meanings of verbalized nouns should always be (a) in a relation of contiguity to the base-noun concepts and (b) compatible with the semantics of the syntactic constructions.